2011
DOI: 10.1021/ja201868d
|View full text |Cite
|
Sign up to set email alerts
|

DNA Electron Injection Interlayers for Polymer Light-Emitting Diodes

Abstract: Introduction of a DNA interlayer adjacent to an Al cathode in a polymer light-emitting diode leads to lower turn-on voltages, higher luminance efficiencies, and characteristics comparable to those observed using a Ba electrode. The DNA serves to improve electron injection and also functions as a hole-blocking layer. The temporal characteristics of the devices are consistent with an interfacial dipole layer adjacent to the electrode being responsible for the reduction of the electron injection barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…DNA has structural features that can facilitate interaction with such conjugated polymers like no other polyelectrolytes can, providing the future possibility of constructing charge transfer nanoassemblies or acting as an injection layer in conjugated polymer light emitting diodes. 8,9 In this work we show that DNA-assisted charge transfer between a donor cationic PPV and acceptor cationic fullerene molecules can approach an efficiency as high as that observed for oppositely charged, cationic PPV and anionic fullerene and that charge transfer efficiency between such same charge sign components can be tuned just by switching ssDNA with dsDNA.Charge transfer between oppositely charged cationic PPV and anionic C 60 . An oppositely charged donor-acceptor (D-A) complex was made using a water soluble, cationic PPV (C-PPV, donor, Fig.…”
mentioning
confidence: 67%
“…DNA has structural features that can facilitate interaction with such conjugated polymers like no other polyelectrolytes can, providing the future possibility of constructing charge transfer nanoassemblies or acting as an injection layer in conjugated polymer light emitting diodes. 8,9 In this work we show that DNA-assisted charge transfer between a donor cationic PPV and acceptor cationic fullerene molecules can approach an efficiency as high as that observed for oppositely charged, cationic PPV and anionic fullerene and that charge transfer efficiency between such same charge sign components can be tuned just by switching ssDNA with dsDNA.Charge transfer between oppositely charged cationic PPV and anionic C 60 . An oppositely charged donor-acceptor (D-A) complex was made using a water soluble, cationic PPV (C-PPV, donor, Fig.…”
mentioning
confidence: 67%
“…Among the various polymers, the DNA and the nucleic acid bases were explored as hole blocking layers (HBL) or effective electron blocking layers (EBL) in Bio Organic light-emitting diodes (BioLEDs) [42][43][44][45], which enhanced the blue and green light emission effectively. As shown in Figure 6, Hagen et al [46] demonstrated that the BioLEDs show a maximum luminous efficiency of about 8 and 1 cdA −1 , respectively.…”
Section: Dna For Other Optical Electronic Devicesmentioning
confidence: 99%
“…Research in -conjugated polymers (CPs) has rapidly developed, driven by many potential applications in organic electronics such as nonlinear optics, organic photovoltaic cells, light-emitting diodes, and field effect transistors [14][15][16][17][18]. The established transition metal (TM)-catalyzed cross-coupling reactions including Kumada, Suzuki, Stille, Negishi, and Heck reaction are powerful and indispensable tools to obtain the desired extended -conjugated systems such as polythiophenes, polyfluorenes, polyphenylenes, poly(arylethynylene)s and so on [19][20][21].…”
Section: Transition Metal (Tm)-catalyzed Crosscoupling Reactionsmentioning
confidence: 99%